Legal Protection for Rape Victims in Indonesia: Seeking an Ideal Concept - Dewi, Aida; Dimyati, Khudzaifah; Subakti, Natangsa; Absori, Absori; Nurani, Siti Syahida (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
This paper analyzes and provides advice on legal protection for rape victims in Indonesia in transcendental, restorative law, and responsive law perspectives. These perspectives are compared and combined in an effort to seek an ideal concept. The implication of this paper is to provide advice for an ideal concept of legal protection for victims of rape in an Indonesian context. This paper uses a normative juridical approach with a legal interpretation method. This paper concludes that law enforcement against perpetrators of rape in the Indonesian context can employ transcendental, restorative law, and responsive law approaches. However, in an effort to find an ideal concept, the transcendental perspective of maṣlaḥah mursalah which considers benefits for the public and prevents harm is more suitable for use in Indonesia’s pluralistic society. This is because, in addition to emphasizing moral, ethical, and religious values ​​in law enforcement, the approach will prevent recurrence of cases through handing out severe punishment to perpetrators of rape and providing physical and psychological rehabilitation to victims to make it in line with restorative justice in which victims get the right to recover physically and mentally without reducing the punishment for rape perpetrators.